Knowledge, physical activity, and control of type 2 diabetes mellitus at Lansot Primary Health Center Tomohon, Indonesia - Desi,; Kalesaran, Angela F. C.; Kaunang , Wulan P. J. (International Journal Of Community Medicine And Public Health, 2023)
Background: It is projected that the global population affected by diabetes mellitus will reach 783.2 million by the year 2045. In Indonesia, there is an anticipated rise of 28.6 million cases of diabetes in the same year. Lansot Primary Health Center has observed a consistent uptick in the prevalence of type 2 diabetes mellitus from 2019 to 2022. The objective was to know the relationship between knowledge level, physical activity, and the control of type 2 diabetes mellitus at Lansot Primary Health Center in Tomohon City. Methods: The study, conducted from March to June 2023 at Lansot Primary Health Center in Tomohon City, Indonesia, used a cross-sectional design and analytical observational techniques. The population were 453 type 2 diabetes patients, and 100 respondents were selected through purposive sampling technique. Variables of interest were knowledge, physical activity, and type 2 diabetes control. Data underwent univariate and bivariate analysis, utilizing a questionnaire as the research instrument. Analysis was performed using SPSS version 29, employing the Chi-Square test. Results: Knowledge among type 2 diabetes patients was sufficient, with moderate physical activity, but suboptimal diabetes control. There was a correlation between knowledge and physical activity with the control of type 2 diabetes, with p value 0.038 and 0.003 respectively. Conclusions: The relationship between knowledge, physical activity, and the control of type 2 diabetes is important. Communities need better information and should engage in regular physical activity. Future studies may explore diverse locations and study designs.